2010
DOI: 10.2337/dc09-1440
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparity in A1C Independent of Mean Blood Glucose in Children With Type 1 Diabetes

Abstract: OBJECTIVEMean blood glucose (MBG) and MBG-independent factors both influence A1C levels. Race was related to A1C independent of MBG in adults. The goal of this study was to determine if racial disparity exists in A1C independent of MBG in children with diabetes.RESEARCH DESIGN AND METHODSParticipants included 276 children with type 1 diabetes. A1C and MBG were obtained from multiple clinic visits, and a hemoglobin glycation index (HGI) (an assessment of A1C levels independent of MBG) was calculated. A1C and HG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 14 publications
6
66
0
Order By: Relevance
“…We noted higher A1C levels in the vitamin D deficient (<37.5 nmol/L) group but this difference was not significant when controlling for ethnicity, suggesting that vitamin D may not exert a significant independent role in metabolic control. Nonetheless the results draw attention to discrepancies in A1C between ethnic groups, a finding previously described (43). Moreover, our study showed an increased risk of vitamin D deficiency in our type 1 diabetes cohort with increasing BMI.…”
Section: Discussionsupporting
confidence: 76%
“…We noted higher A1C levels in the vitamin D deficient (<37.5 nmol/L) group but this difference was not significant when controlling for ethnicity, suggesting that vitamin D may not exert a significant independent role in metabolic control. Nonetheless the results draw attention to discrepancies in A1C between ethnic groups, a finding previously described (43). Moreover, our study showed an increased risk of vitamin D deficiency in our type 1 diabetes cohort with increasing BMI.…”
Section: Discussionsupporting
confidence: 76%
“…Individuals with HbA1c values persistently lower or higher than expected relatively to their blood glucose levels have been identified in several studies where blood glucose was estimated based on fasting plasma glucose [22], self- [18,19,31,32], continuous glucose monitoring data [20,33], and classified as high or low glycators. HGI is a measure of the disagreement between the observed value of HbA1c and the one predicted on the basis of blood glucose levels and it is thought to be an indicator of the degree of hemoglobin glycation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, HbA1c levels were higher in black children from the uppermost SES strata than among the white children in the lowest of our SES echelons. [20][21][22] An analysis of available blood glucose data obtained from meter downloads, however, suggests that the racial disparity in HbA1c was accompanied by a similar disparity in mean blood glucose levels. Language barriers have been suggested to contribute to treatment problems, especially in exclusively Spanish-speaking, lowincome Hispanic families.…”
Section: Figurementioning
confidence: 99%